2014
DOI: 10.1038/srep06718
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 improves the neurological outcome after traumatic brain injury in rats

Abstract: The expression levels of microRNAs (miRNAs) including miR-21, have been reported to change in response to traumatic brain injury (TBI), suggesting that they may influence the pathophysiological process in brain injury. To analyze the potential effect of miR-21 on neurological function after TBI, we employed the fluid percussion injury rat model and manipulated the expression level of miR-21 in brain using intracerebroventricular infusion of miR-21 agomir or antagomir. We found that upregulation of miR-21 level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
113
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 50 publications
5
113
0
Order By: Relevance
“…Consistent with this view of Akt as a key neuroprotective mechanism after CNS injury, others have shown that miR-21, which targets the Akt inhibitor PTEN, is neuroprotective after TBI. 42,43 Although the upregulation of miR-711 occurs rapidly after TBI, it persists for several days suggesting that the therapeutic window for intervention may be significant.…”
Section: Mir-711 Activates Neuronal Apoptosis B Sabirzhanov Et Almentioning
confidence: 99%
“…Consistent with this view of Akt as a key neuroprotective mechanism after CNS injury, others have shown that miR-21, which targets the Akt inhibitor PTEN, is neuroprotective after TBI. 42,43 Although the upregulation of miR-711 occurs rapidly after TBI, it persists for several days suggesting that the therapeutic window for intervention may be significant.…”
Section: Mir-711 Activates Neuronal Apoptosis B Sabirzhanov Et Almentioning
confidence: 99%
“…We then measured the expression of miR-21-5p in neurons, astrocytes, microglias and brain microvascular endothelial cells (BMVECs) respectively using combined miRNA in-situ hybridization and immunofluorescence. We found that compared to astrocytes and microglias, neurons and BMVECs expressed more miR-21-5p, and their miR-21-5p levels are more sensitive in response to injury [18] . We evaluated the influence of miR-21-5p on the neurological outcome of TBI rats using modified neurological severity score and Morris Water Maze.…”
Section: Research Highlightmentioning
confidence: 74%
“…We evaluated the influence of miR-21-5p on the neurological outcome of TBI rats using modified neurological severity score and Morris Water Maze. We found that the increased miR-21-5p level in brain post-injury was beneficial for improving the neurological prognosis of TBI [18] . Then, we observed the impact of miR-21-5p on cellular apoptosis in rats and in-vitro cultured neurons to investigate the mechanism of its protective effect in TBI.…”
Section: Research Highlightmentioning
confidence: 80%
See 2 more Smart Citations